2016
DOI: 10.1007/s00068-016-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

sTREM-1, sIL-2Rα, and IL-6, but not sCD163, might predict sepsis in polytrauma patients: a prospective cohort study

Abstract: Level II-Diagnostic tests and criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, the meta-analysis performed in 2012 covering eleven studies indicated that sTREM-1 in plasma determined individually was not a sufficient biomarker differentiating sepsis from SIRS [103]. In 2016, a cohort study indicated predictive value of sTREM-1 protein as an indicator for sepsis occurrence in patients suffering from polytrauma [104].…”
Section: Triggering Receptor Expressed On Myeloid Cells-1mentioning
confidence: 99%
“…Moreover, the meta-analysis performed in 2012 covering eleven studies indicated that sTREM-1 in plasma determined individually was not a sufficient biomarker differentiating sepsis from SIRS [103]. In 2016, a cohort study indicated predictive value of sTREM-1 protein as an indicator for sepsis occurrence in patients suffering from polytrauma [104].…”
Section: Triggering Receptor Expressed On Myeloid Cells-1mentioning
confidence: 99%
“…It is, however, not without its drawbacks. The test itself is expensive compared with CRP testing, and while PCT increases are more specific for bacterial infections than CRP or ESR, false-positive results may be observed in such cases as acute respiratory distress syndrome, chemical pneumonitis, severe falciparum malaria, and others ( 32 ). It is important to note that trauma and subsequent tissue damage may, and often do, induce sepsis via release of inflammatory compounds and subsequent perpetuation of the immune response.…”
Section: Procalcitonin and C-reactive Proteinmentioning
confidence: 99%
“…It is important to note that trauma and subsequent tissue damage may, and often do, induce sepsis via release of inflammatory compounds and subsequent perpetuation of the immune response. However, high values for biomarkers other than PCT are more indicative of classical bacterial sepsis than trauma ( 32 ). This is at least partially because PCT rises higher in correlation with the severity of an infection, whereas CRP quickly reaches a plateau no matter the source or comparative severity of inflammation ( 33 ).…”
Section: Procalcitonin and C-reactive Proteinmentioning
confidence: 99%
“…Thus, combination therapy with checkpoint inhibitors may provide a viable solution for enhancing the antitumor effect of the CAR T-cells, as it was proven by the team of O’Rourke et al in solid malignancies ( 140 ). A good strategy would be to develop the so-called armored CARs, which also express the very efficient cytokine IL-12, which has a pleiotropic on both innate and adaptive T lymphocytes ( 141 ). To further augment the antitumor activity, the fourth-generation CAR that contains a transduction domain to promote production of a T-cell-activating cytokine such as IL-12 (so-called armored CAR T) are currently being researched ( 174 , 175 ).…”
Section: Genetic Engineered T-cells For the Immunotherapy Of Allmentioning
confidence: 99%